Long-Term Biocompatibility of a Highly Viscously Thiol-Modified Cross-Linked Hyaluronate as a Novel Vitreous Body Substitute - Jose Hurst; Annekatrin Rickmann; Nele Heider; Christine Hohenadl; Charlotte Reither; Andreas Schatz; Sven Schnichels; Kai Januschowski; Kai Januschowski; Martin S. Spitzer; Martin S. Spitzer (Frontiers Media S.A., 2022)
Purpose: In surgical ophthalmology, the treatment of complicated retinal and vitreous diseases is one of the central challenges. For this purpose, the vitreous body is removed as part of the standard therapy and replaced by a temporary tamponade to stabilize the position of the retina. Since the tamponading properties of previous materials such as silicone oils, gases, or semi-fluorinated alkanes are a combination of their surface tension and their buoyancy vector, they cannot completely fill the vitreous cavity. The aim of this work was to test in vivo a novel vitreous body substitute (ViBos strong) based on cross-linked hyaluronic acid for its compatibility.Methods: A pars plana vitrectomy with posterior vitreous detachment was performed in the right eye of 18 pigmented rabbits, with subsequent injection of ViBos strong. Follow-up examination included slit-lamp examination, funduscopy, intraocular pressure measurements (IOP), optical coherence tomography (OCT), and electroretinogram (ERG) measurements. The rabbits were sacrificed at three different time points (1, 3, and 6 months; each 6 animals) and examined macroscopically and prepared for histological examination (HE staining) and immunohistochemistry (Brn3a and glial fibrillary acidic protein (GFAP)).Results: ViBos strong demonstrated good intraoperative handling and remained stable for at least 1 month and degraded slowly over 6 months. IOP was within clinical acceptable values at all follow-up examinations. Retinal function was well preserved after instillation of the hydrogel and comparable to the untreated eye after 6 months in OCT, ERG, and histological examinations. An increase in the GFAP expression was found in the surgery eyes, with a peak in the 3-month group. The Brn3a expression was not significantly affected by vitrectomy with ViBos strong.Conclusion: Highly viscously thiol-modified cross-linked hyaluronate showed a good biocompatibility in rabbit eyes over 6 months after vitrectomy, making it a promising potential as a vitreous substitute.